Towards a Definition for Health Care–Associated Infection. (23rd May 2018) - Friedman, N Deborah; Levit, Dana; Taleb, Eyal; Marcus, Gil; Michaeli, Leah; Broide, Mor; Mengesha, Bethlehem; Zaidenstein, Ronit; Lazarovitch, Tsilia; Dadon, Mor; Kaye, Keith S; Marchaim, Dror
Abstract: Background: Health care–associated infection (HcAI) is a term frequently used to describe community-onset infections likely to be caused by multidrug-resistant organisms (MDROs). The most frequently used definition was developed at Duke University Medical Center in 2002 (Duke-2002). Although some professional societies have based management recommendations on Duke-2002 (or modifications thereof), neither Duke-2002 nor other variations have had their performance measured. Methods: A case–control study was conducted at Assaf Harofeh Medical Center (AHMC) of consecutive adult bloodstream infections (BSIs). A multivariable model was used to develop a prediction score for HcAI, measured by the presence of MDRO infection on admission. The performances of this new score and previously developed definitions at predicting MDRO infection on admission were measured. Results: Of the 504 BSI patients enrolled, 315 had a BSI on admission and 189 had a nosocomial BSI. Patients with MDRO-BSI on admission (n = 100) resembled patients with nosocomial infections (n = 189) in terms of epidemiological characteristics, illness acuity, and outcomes more than patients with non-MDRO-BSI on admission (n = 215). The performances of both the newly developed score and the Duke-2002 definition to predict MDRO infection on admission were suboptimal (area under the receiver operating characteric curve, 0.76 and 0.68, respectively). Conclusions: Although the term HcAI is frequently used, its definition does not perform well at predicting MDRO infection present on admission to the hospital. A validated score that calculates the risk of MDRO infection on admission is still needed to guide daily practice and improve patient outcomes.